2018
DOI: 10.18632/oncotarget.25768
|View full text |Cite
|
Sign up to set email alerts
|

ST2/IL-33 signaling promotes malignant development of experimental squamous cell carcinoma by decreasing NK cells cytotoxicity and modulating the intratumoral cell infiltrate

Abstract: Squamous cell carcinoma (SCC) is the second most common form of skin cancer and the mechanism(s) involved in the progression of this tumor are unknown. Increases in the expression of IL-33/ST2 axis components have been demonstrated to contribute to neoplastic transformation in several tumor models and interleukin-33 is correlated with poor prognosis of patients with squamous cell carcinoma of the tongue. Based on these observations, we sought to determine the role of the IL-33/ST2 pathway during the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…The authors also demonstrated that hypoxia is crucial for N2 phenotype maintenance and tumor oxygenation can revert TANs phenotype toward N1 ( Mahiddine et al, 2020 ). Tumor-associated macrophages (TAMs) also represent a significant percentage of infiltrating phagocyte population in SCC ( Kambayashi et al, 2013 ; Amôr et al, 2018 ; Simonneau et al, 2018 ; Jiang et al, 2019 ), and specific depletion of these cells inhibited tumor growth ( Takahashi et al, 2009 ). The recruitment of monocytes into the SCC is mediated by CC chemokines such as CCL2 and, once in the TME, monocyte-derived macrophages are polarized toward a M1 or M2 phenotype ( Pettersen et al, 2011 ; Caley et al, 2020 ).…”
Section: Cellular Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also demonstrated that hypoxia is crucial for N2 phenotype maintenance and tumor oxygenation can revert TANs phenotype toward N1 ( Mahiddine et al, 2020 ). Tumor-associated macrophages (TAMs) also represent a significant percentage of infiltrating phagocyte population in SCC ( Kambayashi et al, 2013 ; Amôr et al, 2018 ; Simonneau et al, 2018 ; Jiang et al, 2019 ), and specific depletion of these cells inhibited tumor growth ( Takahashi et al, 2009 ). The recruitment of monocytes into the SCC is mediated by CC chemokines such as CCL2 and, once in the TME, monocyte-derived macrophages are polarized toward a M1 or M2 phenotype ( Pettersen et al, 2011 ; Caley et al, 2020 ).…”
Section: Cellular Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
“…Due to its central role in mediating type 2 innate and adaptive immunity via the ST2 receptor, IL-33 has been extensively studied in cancer and inflammatory diseases ( Liew et al, 2016 ). In mice, IL-33 promotes SCC development by increasing M2 macrophage infiltration and decreasing NK cell cytotoxicity ( Amôr et al, 2018 ; Figure 2G ). IL-33 promotes differentiation of macrophages that in turn, send paracrine TGF-β signals to tumor cells consequently inducing invasive behavior ( Taniguchi et al, 2020 ; Figure 2G ).…”
Section: Evasion Of the Immune Response: Potential Targets For Immunomentioning
confidence: 99%
“…NK cells play a critical role in suppressing cSCC development in murine models [39], though the TME may modulate their cytotoxicity through downregulation of activating receptors [53]. Genetic or acquired impaired function or reduced number of NK cells is associated with increased risk of herpesvirus, papillomavirus, and cSCC in humans [54,55,56,57].…”
Section: The Role Of Innate Immunitymentioning
confidence: 99%
“…It has been shown that exogenous IL-33 enhanced the infiltration of CD4 + , CD8 + T cells and tumor antigen-specific CD8 + T cells in established melanoma. Moreover, there is significantly increased IFN-γ production and KLRG1 expression in tumor-infiltrating CD8 + T cells after applying exogenous IL-33 (8)(9)(10). Main outcome of these changes is enhancement of antitumor immune response.…”
Section: Role Of Interleukin 33 In Biology Of Tumor and Antitumor Immmentioning
confidence: 99%